2020
DOI: 10.1002/rcs.2123
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of robot‐assisted vs video‐assisted and traditional open thoracic surgery for lung cancer: A systematic review and network meta‐analysis

Abstract: Background: The superiority of robot-assisted thoracic surgery (RATS) over videoassisted thoracic surgery (VATS) and thoracotomy remains controversial for lung cancer. Methods: A network meta-analysis (NMA) and pairwise meta-analysis (PMA) were performed to evaluate the perioperative outcomes using five databases. Results: Thirty-two studies involving 6593 patients were included for analysis. The NMA showed that RATS had similar operative time, conversion rate to thoracotomy, number of lymph node, postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 80 publications
1
25
0
Order By: Relevance
“…As a quickly evolving, next-generation minimally invasive technique, RATS has increasingly grown in popularity in recent years. The robotic platform has some technical advantages over VATS, including a three-dimensional operative view, intuitive use of the robotic hands, and increased instrument flexibility; therefore, it has the potential to surpass VATS in the handling of more complex cases and may facilitate lymph node dissection (3)(4)(5)(6). Currently, RATS requires 3 or 4 ports and 1 or 2 assistive incisions.…”
Section: Introductionmentioning
confidence: 99%
“…As a quickly evolving, next-generation minimally invasive technique, RATS has increasingly grown in popularity in recent years. The robotic platform has some technical advantages over VATS, including a three-dimensional operative view, intuitive use of the robotic hands, and increased instrument flexibility; therefore, it has the potential to surpass VATS in the handling of more complex cases and may facilitate lymph node dissection (3)(4)(5)(6). Currently, RATS requires 3 or 4 ports and 1 or 2 assistive incisions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in an analysis of patients with rectal cancer investigators reviewed claims data from 2005 through 2017, reporting decreased LOS for robotic surgery as compared to open surgery [ 13 ]. In contrast, although the lung cancer literature reveals reductions in hospital LOS for minimally invasive approaches as compared to open lung surgery [ 8 ], analyses of robotic lung surgery have not demonstrated appreciable gains in LOS as compared to VATS [ 2 , 15 ]. In kidney cancer, reduced LOS has been demonstrated for MIS vs open modalities, however the literature comparing robotic and laparoscopic modalities has demonstrated inconsistent results [ 16 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, data from the Norwegian Registry for Gastrointestinal Surgery and from the Norwegian Colorectal Cancer Registry also revealed lower conversion rates with robotic-assisted rectal resections compared with conventional laparoscopic resections [ 20 ]. In the same manner, meta-analyses of patients with lung cancer have similarly identified lower conversion to open surgery for patients who underwent robotic surgery as compared to video-assisted surgery [ 15 , 21 ]. Although not all studies have demonstrated fewer conversions with robotic surgery [ 7 ], our data convincingly demonstrate significant reductions in conversions in all studied procedures except for nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The application of RATS is becoming increasingly common in several surgical disciplines (such as urology, gynecology, and cardiac surgery) owing to its optimal operability and minimal invasiveness (12)(13)(14)(15). Previous studies have indicated that RATS reduces intraoperative bleeding, chest tube drainage, and hospitalization stay compared to thoracotomy in early-stage NSCLC patients (15)(16)(17). RATS has also been shown to reduce postoperative pain compared to thoracotomy in stage I−IIIA NSCLC patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…RATS has also been shown to reduce postoperative pain compared to thoracotomy in stage I−IIIA NSCLC patients (18). Regarding safety, postoperative complications of RATS have been demonstrated to be similar those of thoracotomy in early-stage NSCLC patients (17,19). However, RATS may increase the overall cost and incur a large economic burden on patients (18,20,21).…”
Section: Discussionmentioning
confidence: 99%